Global imbalances and the current account adjustment process: An empirical analysis - Marius Tippkötter (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper investigates the impact of the exchange rate regime on the current account adjustment process. In a first step, the present analysis assesses previous empirical work supporting the predominant view that more flexible exchange rate regimes facilitate current account adjustments. Using a FGLS estimator with fixed effects and panel corrected standard errors, the author draws upon the methodological approaches of two pertinent papers. The data set encompasses data for 171 countries for the 1970 to 2008 period. According to the fixed effects estimations, evidence in favor of the conventional wisdom does not prove to be robust. After pointing out fundamental weaknesses of the fixed effects estimator within this context, the author performs a dynamic panel estimation using a System GMM estimator fully developed in Blundell and Bond (1998). The results of this approach stand in contrast to the previous estimations, providing solid empirical evidence in favor of the predominant view. A monotonic relationship between exchange rate regime flexibility and the rate of current account reversion can be observed, indicating faster current account convergence for more flexible regimes. By employing an estimator that is more germane to the issue under investigation, the paper fills an important gap between economic common sense and its underlying empirics.
Keywords: F31; F32; 330; Current account adjustment process; current account imbalances; exchange rate regime flexibility; Zahlungsbilanzmechanismus; Zahlungsbilanzungleichgewicht; Wechselkurssystem; Flexibler Wechselkurs; Panel; Momentenmethode; Schätzung; Welt